NH3 gas detection with graphene field effect transistors - Tay, Jason Zhi Wei. (2013)
This report was written by a student for his final year project mentioned about what was done and learnt throughout the project’s time line. The aim of his project is to study, carry out various test experiment under several different conditions and investigate the characteristics of the given graphene based field effect transistors (G-FET) which functions as an ammonia gas detection sensor. Although the device had been fabricated, the student had learnt the theoretical process steps from his mentor. The student grew graphene using thermal chemical vapour deposition, transferring and characterization of the grown graphene. The process of fabricating the graphene FET was also learnt. The project also includes charactisation of the fabricated GFET to select some good working transistors with a suitable transfer curve, Id-Vg curve for gas sensing application. The graphene base sensing device was then put to gas detection test. This report includes experimental results of its response to ammonia gas, recovery test and observing dirac point shift due to various method like heating or electrical means.